Protection of civilians in International Humanitarian Law: An appraisal - Ali Mohamed, Ashgar Ali (LexisNexis, 2016)
The article briefly refers to the applicable law, its adequacy, its compatibility with relevant rules of Islamic Law which applies to Muslims, highlights the main impediments to protecting civilians and suggests the taking of some positive actions to end the culture of impunity and promote the culture of protection.